The Effect of Cooperative Learning Model Two Stay Two Stray (TSTS) Type on Student Motivation and Learning Outcomes on Science of the Fifth Grade Students of SDN 15 Palu - Wildana, Wildana; Rede, Amran; Afadil, Afadil (Jurnal Riset Pendidikan MIPA, 2019)
The study of the effect of cooperative learning model two stay two stray types on motivation and learning outcomes of the fifth-grade students of SDN15 Palu was carried out from March to June 2018. This study used quasi-experimental methods. The research design used the Pretest-Posttest Control Group Design. Data collection techniques used questionnaires and test results. The data analysis technique used the t-test inferential statistical method. The study population was fifth-grade students of SDN15 Palu. The sample of the research was Va class with as many as 29 people as the experimental group and Vb class with 28 people as the control group, which was determined by purposive sampling technique. The independent variable in this study was the TSTS model, while the dependent variable was a motivation and learning outcomes. Based on hypothesis testing with two-party t-test statistics obtained students learning motivation with t count was higher than t table (7.876 > 2.004). Student learning outcomes obtained tcount higher than t table (3.654 > 2.004). These results indicated that the application of cooperative learning model two stay two stray type influences the motivation and learning outcomes of the science of the fifth-grade students of SDN 15 Palu.